Structures of 2,5-diaryl- and 2,3,5,6-tetra[3,2-b]thiophene synthesized by the palladium-catalyzed Suzuki-Miyaura cross-coupling reaction - Hien, Nguyen; Ngan, Nguyen Bich; Dat, Nguyen Dang; Meervelt, Luc van (Vietnam Journal of Chemistry, 2016)
The crystal structures of 2,5-di(ethoxyphenyl)-3,6-dibromothieno[3,2-b]thiophene (I) and 2,5-di(ethoxyphenyl)-3,6-diphenylthieno[3,2-b]thiophene (II) have been studied in order to evaluate the planarity of these molecules. The aromatic systems introduced to the thieno[3,2-b]thiophene core structure show a degree of rotation from 30.94° to 66.56°. The crystal packing of (I) are characterized by π×××π stacking, while in (II), C-H×××p and C-H×××O interactions are observed.